Potencjał kadrowy organizacji - Kolman, Romuald (Human Resources Potential of an Organization, 2008)
The paper presents the analytical method for computation of capability of human resources of any organization. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 477-481